Nest survival of the Two-Banded Plover (Charadrius falklandicus) population in Northern Chubut Province, Patagonia Argentina - Hevia, Glenda Denise (2016)
Current efforts to monitoring the Two-Banded Plover (Charadrius falklandicus), an endemic shorebird to southern South America, have provided information on their breeding biology at beaches with human disturbance in northern Patagonia, Argentina. We estimate annual nest survival and describe causes of nest failure at two beaches with high and low levels of human disturbance located in Puerto Madryn (42°S, 65°W). Fieldwork surveys were conducted by foot using the nearest road track between October and December, 2012. We recorded spatial coordinates of each nest and the distance to the: high tide line, road track, nearest con-specific nest. We floated eggs to estimate hatching dates and nests were monitored 3-5 weekly to verify success (≥1 egg hatched) or failure (human impact, flooding, abandoned, and predation). We used encounter histories for 41 nests found throughout an 89-day nesting season to estimate the DSR (Daily Survival Rate) from the beginning of incubation and analyze competing models with RMark package in R. The most common cause of nest failure at Parana was human impact: vehicles trampled eggs (80%, n=7), followed by predation (20%, n=2). By contrast, at Las Canteras the most common cause was flooding by extraordinary high tides (50%, n=3), followed by parental abandonment (33%, n=2) and human impact (17%, n=1). The DSR was highest in Las Canteras (0.983; n=22), than in Parana (0.966; n=19). Management actions to protect plovers from harmful human disturbance are urgently need it.